Identification and assessment of man-made threats to cities using integrated Grey BWM- Grey MARCOS method - Bitarafan , Mahdi; Amini Hosseini, Kambod; Zolfani, Sarfaraz Hashemkhani (Decision Making: Applications in Management and Engineering, 2023)
Identifying and evaluating any threat against the critical infrastructures, including history, methods, abilities, and motivations, is essential for crisis management and cities' passive defense. Threats, including natural and unnatural (man-made), are directed at cities' critical assets and infrastructures. Essential assets are considered valuable components, so the slightest malfunction or damage to the body causes damage to the system. This study uses Tehran, the capital of Iran, as a case study to identify and assess man-made dangers to cities and their vital resources. This work creates an innovative integrated MCDM approach that can handle information ambiguity in crisis management. Therefore, at this stage of identifying man-made threats, library methods and interviews with experts were used, and multi-criteria decision-making techniques were implemented. Moreover, this research benefits from the grey Best-Worst method (BWM) to evaluate the research criteria and grey Measurement of Alternatives and Ranking according to COmpromise Solution (MARCOS) to rank the threats. The research findings indicated that the three main threats to Tehran city are cyber, military, and terrorist attacks. Finally, a sensitivity analysis based on two practical experiments is done, and research results are verified.